IMPLEMENTASI PROTOTIPE ALAT UKUR KERENTANAN LISTRIK (SUSEPTOMETER) BAHAN ANISOTROP BERBASIS KAPASITOR KEPING SEJAJAR - Yuhelsa Putra (Universitas Sultan Ageng Tirtayasa, 2015)
The prototype chip capacitor as a parallel electric field sensors and sources, as well as the operational amplifier type of instrumentation. Prototype measuring devices are capable of measuring the electric susceptibility of dielectric material (wood and water), paraelectric (aluminum) and ferroelectric materials (iron).Voltage magnitude of the measured material processed using a graphical method to obtain the value of the gradient. From this gradient an electric susceptibility values obtained material. Measurement values and theoretical comparison of the results obtained 0.9 ± 0.2. The results of of measurements of electrical vulnerability of wood close to the value 8, while the electric susceptibility measurement results obtained water at 81 ±2. The value of iron and aluminum electric susceptibility values approaching infinity. Value of electric susceptibility of these materials tend to approach the value of his theory, it is feasible prototype gauge used to measure the electric susceptibility of dielectric materials ,ferroelectric paraelectric and especially iron.